2017
DOI: 10.1016/j.nedt.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Widening participation in nurse education: An integrative literature review

Abstract: Whilst widening participation is a key issue for both nurse education and the wider profession there is a lack of conceptualisation and focus regarding mechanisms to both encourage and support a wider diversity of entrant. Whilst there are some studies, these focus on particular individual widening participation groups rather than a wider strategic focus across the student lifecycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…The studies on retention and success clustered around the academic experience, particularly overcoming academic challenges, and the provision of additional student support. The more recent review of the literature about WP in nurse education (Heaslip et al, 2017) identified ten empirical studies, and similar themes emerged in relation to both access and success. The focus of much of the work is on academic barriers to participation and the construction of alternative entry pathways.…”
Section: Learning From the Literaturementioning
confidence: 85%
See 2 more Smart Citations
“…The studies on retention and success clustered around the academic experience, particularly overcoming academic challenges, and the provision of additional student support. The more recent review of the literature about WP in nurse education (Heaslip et al, 2017) identified ten empirical studies, and similar themes emerged in relation to both access and success. The focus of much of the work is on academic barriers to participation and the construction of alternative entry pathways.…”
Section: Learning From the Literaturementioning
confidence: 85%
“…Underpinning this paper are the assumptions that first, widening participation (WP) is necessary to recruit sufficient numbers of staff to meet demand from healthcare providers, and second that diversity of the healthcare workforce contributes to the quality of the care provided (Heaslip et al 2017). WP is understooad to mean expanding the diversity of students entering and succeeding in HE, with a particular focus on those from underrepresented and disadvantaged groups.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, policy changes to tertiary education funding have placed an increasing financial burden on students (Devlin, James, & Grigg, ; Robotham, ). Concomitantly, the student demographic profile is diversifying in response to widening participation initiatives, with increasing numbers of “first‐in‐family” and mature‐aged students (Heaslip, Board, Duckworth, & Thomas, ; Robotham, ). In Australia, over half of all students enrolled in nursing degrees are nonschool leavers (Australian Bureau of Statistics, ) with a similar picture in the UK, where a quarter of all commencing students are over 30 years of age (Keogh, ).…”
Section: Introductionmentioning
confidence: 99%
“…Heaslip et al. conducted a literature review into the extent of WP within the UK nursing profession . They revealed a paucity of research into groups targeted by nursing WP initiatives and retention rates for under‐represented nursing graduates.…”
mentioning
confidence: 99%